2021
DOI: 10.11648/j.tecs.20210602.12
|View full text |Cite
|
Sign up to set email alerts
|

School Climate Indices as Predictors of Teacher Job Satisfaction and Performance in Oyo State, Nigeria

Abstract: School climates indices as predictors of teacher job satisfaction and performance in Oyo State of Nigeria were investigated in this study. The school climate indices include; school laboratories, libraries, classrooms and instructional materials. This was a descriptive survey research which was questionnaire based. The population of the study was all public secondary school teachers in Oyo State, Nigeria. Multi-stage using cluster and simple random sampling techniques to select a total of one thousand and five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
0
0
Order By: Relevance
“…Kyriacou's [78] review of the literature demonstrated that inequity was one of the sources of stress most frequently reported by teachers [79]. At the same time, several studies have shown that organizational justice was a critical factor in defining well-being in school [51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kyriacou's [78] review of the literature demonstrated that inequity was one of the sources of stress most frequently reported by teachers [79]. At the same time, several studies have shown that organizational justice was a critical factor in defining well-being in school [51].…”
Section: Discussionmentioning
confidence: 99%
“…Implicit in these definitions is the importance of both affect and cognition. Thus, when people evaluate their jobs, both thinking and feeling are involved [51]. Studies have found job satisfaction to have significant positive relationships with happiness [52] and emotional, psychological, and social well-being [13,53,54].…”
Section: Job Satisfaction and Mental Well-beingmentioning
confidence: 99%
See 1 more Smart Citation